N-substitution of polybenzimidazoles: synthesis and evaluation of physical properties - Kumbharkar, Santosh C.; Kharul, Ulhas K. (European Polymer Journal, 2009)
Series of N-substituted polybenzimidazoles (PBI) were synthesized using selective alkyl groups with varying bulk and flexibility, viz., methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. PBl-I based on 3,3'-diaminobenzidine (DAB) and isophthalic acid and PBI-Bul based on DAB and 5-tert-butyl isophthalic acid were chosen for N-substitution. Structural characterizations of substituted polymers by FT-IR and (1)H NMR revealed elimination of hydrogen bonding. Evaluation of their physical properties revealed that N-substitution rendered better solvent solubility in common organic solvents, more open polymer matrix, but reduced thermal properties in comparison to their respective parent PBI. 4-tert-butylbenzyl, methylene trimethylsilane or n-butyl group substituted polymers were soluble even in chlorinated solvents (CHCl(3) and TCE). Substantial variations in gas permeability of inert gases, He and Ar and attractive P(He)/P(Ar) selectivity, especially after methyl group substitution depicted potential of these materials for gas separation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; hydrogen bonding; N-Substitution; Polybenzimidazole